Applying multi-criteria approaches to ontology ranking: a comparison with AKTiveRank. (1st January 2012) - Esposito, Alessandra; Tarricone, Luciano; Zappatore, Marco
Recent years have seen a progressive spread of ontologies. This indicates the need for instruments for their evaluation and ranking. However, most of the developed algorithms are based on a single metric, thus focusing on a unique feature and neglecting other potentially meaningful aspects. Others perform a weighted aggregation of different metrics, thus resulting in poor tunability and sensitivity to measurement errors. In this context, we propose the adoption of general purpose and flexible multi-criteria decision analysis techniques which represent a total novelty for ontologies. Two methods belonging to the Electre family are presented: Electre I and Electre III. Both techniques are compared to the well-known AKTiveRank procedure, demonstrating their suitability for ontology ranking. The former best identifies the most promising candidates amongst a set of alternatives. The latter provides a set of tuning parameters for making thin ranking procedures.